Integration of Portable PCR and a Lateral Flow Assay for the Rapid Detection of HPV Type 16 - Yusuf M; Rohmatulloh FG; Soidah S; Gaffar S; Mantilidewi KI; Winarno GNA; Hidayat YM; Subroto T (Medical Devices: Evidence and Research, 2025)
Muhammad Yusuf,1,2 Fauzian Giansyah Rohmatulloh,2 Siti Soidah,2 Shabarni Gaffar,1 Kemala Isnainiasih Mantilidewi,3 Gatot Nyarumenteng Adhipurnawan Winarno,3 Yudi Mulyana Hidayat,3 Toto Subroto1,2 1Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 2Research Center for Molecular Biotechnology and Bioinformatics, Universitas Padjadjaran, Bandung, West Java, 40133, Indonesia; 3Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, 45363, IndonesiaCorrespondence: Muhammad Yusuf, Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia, Email m.yusuf@unpad.ac.idBackground: Human papillomavirus (HPV) is a leading cause of cervical cancer worldwide, with HPV type 16 accounting for roughly half of cases. Although polymerase chain reaction (PCR) is considered the gold standard for HPV detection, its reliance on gel electrophoresis can be costly and require specialized facilities.Objective: We developed a diagnostic approach integrating PCR with a lateral flow assay to detect HPV type 16 using gold nanoparticles as visible labels.Methods: Primers targeting the L1 gene of HPV 16 were labeled with 6FAM (forward) and biotin (reverse). Amplified products were applied to lateral flow strips preloaded with streptavidin–gold nanoparticle conjugates. Visible red bands on the test and control lines indicated successful detection.Results: The optimized assay produced a clear band at ~333 bp by gel electrophoresis and yielded distinct red lines on the lateral flow strip for positive samples. Compared to electrophoresis, this format has a faster turnaround and can reduce costs by eliminating bulky equipment.Conclusion: This simplified and cost-effective method provides a user-friendly alternative to traditional electrophoresis, making it suitable for resource-limited settings. Further large‐scale clinical validation is warranted, including cost analyses and multiplexing for additional genotypes.Keywords: HPV type 16, PCR, lateral flow assay, cervical cancer diagnostics, gold nanoparticles